2020
DOI: 10.1080/1828051x.2020.1783378
|View full text |Cite
|
Sign up to set email alerts
|

Study of faecal parameters and body condition in dogs with a diet supplemented with Lactobacillus acidophilus D2/CSL (CECT 4529)

Abstract: The aim of our case-control study is to evaluate the effects of a diet integrated with the probiotic Lactobacillus acidophilus D2/CSL (CECT 4529) on the nutritional status and faecal consistency of healthy dogs belonging to the English Cocker Spaniel (ECS) and Labrador Retriever (LR) breeds. A total of 30 dogs were enrolled in this study, and they were randomly assigned to a Control (CTR, n ¼ 14) and a Treated group (LACTO, n ¼ 16). The trial consisted in a 7-days adaptation period where all the animals receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…A diet rich in dietary fibres/butyrate can reduce diseases like obesity, diabetes, cardiovascular diseases, gastrointestinal imbalances and also some cancer diseases. In addition, inflammatory processes can also be alleviated by butyrate such that a faster recovery can occur [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. With regard to the bacterial colonization when rye and fermented rye were added, there were hardly any differences in faeces, so it can be stated that the fibre components important for the colon flora remain relatively untouched by a preceding fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…A diet rich in dietary fibres/butyrate can reduce diseases like obesity, diabetes, cardiovascular diseases, gastrointestinal imbalances and also some cancer diseases. In addition, inflammatory processes can also be alleviated by butyrate such that a faster recovery can occur [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. With regard to the bacterial colonization when rye and fermented rye were added, there were hardly any differences in faeces, so it can be stated that the fibre components important for the colon flora remain relatively untouched by a preceding fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…This result could be justified by the presence of Lactobacillus acidophilus in the new administered product combined with the fructooligosaccharides that make the probiotic more effective. In particular, the effects of Lactobacillus acidophilus D2/CSL (CECT 4529) on fecal parameters and body condition in dogs and cats have been recently studied [18,19]. In addition, a study on dogs with CKD treated with multi-strain probiotics containing Lactobacillus showed a significant improvement in Glomerular filtration rate (GFR) and USG and a significant reduction of UPC compared to the control [7].…”
Section: Discussionmentioning
confidence: 99%
“…For all of these reasons, the choice of probiotics (e.g., Lactobacilli spp. and Bifidobacteria), prebiotics (e.g., fructooligosaccharides and galactooligosaccharides), and antioxidants (e.g., vitamin E, carotenoids, lutein, vegetable oil) has increased in both human and veterinary medicine [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The TG group received the supplement (Renal N, Candioli s.r.l., Italy) for 90 days. It contains L. acidophilus D2/CSL (30 mg/ day) (Bruni et al 2020), fructooligosaccharides (400 mg/day) and Olea Europaea extract (40 mg/day) (Supplementary Appendix 1) . The CG received the placebo for the same period of time (Supplementary Appendix 1).…”
Section: Supplement and Dietmentioning
confidence: 99%
“…The use of ingredients in the diet that have an effect directly on the renal function or through a secondary product mediated by the microbiome can be beneficial for patients with renal disease. Therefore, in order to maintain a correct balance of the gastrointestinal microbiota, the use of probiotics, prebiotics and antioxidants has increased in humans as well as in animals (Rose et al 2017;Fusi et al 2019;Bruni et al 2020;Saettone et al 2020). Lactobacillus and Bifidobacterium are the most widely used probiotics in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%